Da capital bandeirante às imagens do cinema institucional de São Paulo (1930-1940) - Santos, Márcia Juliana (2011)
In this work, researching the1930s and 1940 with the aim to identify in natural films, posed, current affairs, documentaries and newsreels produced or commissioned by government agencies, discourses and understandings that were crucial to building diverse images of the city of São Paulo. We investigated several aspects that permeated the time interval between the crisis of fictional production (posed) in São Paulo, from and dated from the early 1930s, until the rise of the studios in São Paulo, from 1949, with the inauguration of Vera Cruz. An important film experience was done in the meantime, over the city, but not investigated or was questioned by historiography. In the period, non-fiction production has intensified, partly to meet a government demand to register, through film, urban change, social policies and they passed the state capital. We started from the practice of domestic and foreign cameraman to identify different cultural references, steeped in historical and social production. From the methodological point of view, work with sources (movies, newspapers, interviews, magazines, reports etc.) at all times sought to follow the paths of realization of these films. Both the government at the municipal, state and federal governments, as the modernist writers of São Paulo, analyze or produce film or immigrants living orders of the films contributed to the creation of images on the capital city. It has been argued by several sources of confrontation that was this production that started in the cinema, a way of telling a story with official advertisement objectives or documentary about the city